The ANTIPLASMODIAL AND Β-HEMATIN INHIBITORY POTENTIAL OF THE EXTRACT AND SOLVENT FRACTIONS OF NEPHROLEPIS UNDULATA - AKOSILE, Oluwayomi Rebecca; Odediran, Samuel Akintunde; BAMIGBOYE, Rachael Adebola; ADEBAYO, Praise Adetola; ADEBOLU, Deborah Abimbola (African Journal of Traditional, Complementary and Alternative Medicines, 2024)
Background: The beta-hematin-inhibitory potential of the extract and the partitioned fractions of Nephrolepis undulata have not been determined, neither the likely constituents responsible for the observed in vivo antiplasmodial activities identified, hence this study. Materials and Methods: The methanol extract of N. undulata (MNU), was evaporated in vacuo and subsequently partitioned to give HNU (n hexane), DNU (dichloromethane), ENU (ethyl acetate) and ANU (aqueous phase) which were investigated in vivo in mice at 0-800mg/kg against chloroquine-sensitive Plasmodium berghei berghei using Peter’s four-day test. The Beta hematin inhibition assay was carried out on the extract and the fractions as well as Gas Chromatography Mass Spectroscopy for identification of the chemical constituents. Normal saline and chloroquine (10mg/kg) were negative and positive controls, respectively. All the results were subjected to statistical analysis using ANOVA with Student Newman Keul’s as post hoc test. Results: The partitioned fractions elicited comparatively lower percentages chemosuppression/inhibition and higher effective doses/inhibitory IC50 compared to NU in both experiments respectively suggesting that the constituents were acting synergistically. The GC-MS analysis revealed a total of eleven compounds in MNU partitioned into HNU: Neophytadiene, Hexadecanoic acid methyl ester, N–Hexadecanoic acid, 10 octa decenoic acid methyl ester and Methyl stearate, DNU: 2 ethyl acridine, ENU: Benzoic acid methyl ester and ANU: Benzoic acid methyl ester, 2 ethyl acridine while additional five compounds found in MNU were not detected in any of the fractions. Conclusion: The constituents of the antimalarial MNU seem to be acting synergistically to inhibit haemozoin formation in the parasite.